Originally Posted by

**dolkam** Hello.

I must "use the binomial theorem to determine the coefficient x^14 in the expansion of (3x^2-1/3)^16".

I find that:

n=16

r=14

a=3x^2 (I believe)

b=-1/3

I write that (sorry but the matrix brackets I cannot make):

(16) (3x^2) ^(16-14+1) (-1/3)^13

(13)

= (16) (3x^2)^3 (-1/3)^13

(13)

= (16!/(16-13)!13!) (1/? x^6)

This part is how I am getting confused.

Can somebody help me please to continue to solving this question? I must "expressing the coefficient as a fraction in lowest terms" but I don't think I have calculated well above to make the fraction to continue. The book is not showing this kind of difficult examples before we must do the assignment!

Thank you.

Brigitte